Acoustic Radiation Force Impulse (ARFI) elastography imaging of equine distal forelimb flexor structures - Bernardi, N. S. [UNESP]; Feliciano, M. A. R. [UNESP]; Gravena, K. [UNESP]; Avante, M. L. [UNESP]; Simoes, A. P. R. [UNESP]; Uscategui, R. A. R.; Dias, D. P. M. [UNESP]; Lacerda Neto, J. C. [UNESP] (Arquivo Brasileiro Medicina Veterinaria Zootecnia, 2020)
This study set out to determine normal values for acoustic radiation force impulse (ARFI) elastography of the superficial digital flexor tendon, deep digital flexor tendon, accessory ligament of the deep digital flexor tendon and suspensory ligament in horses. Twenty-four horses were submitted to conventional sonographic assessment and elastography imaging (quantitative ARFI method) of distal forelimb tendons and ligaments at nine anatomical regions. Elastograms depicted tendons and ligaments in orange to red tones consistent with greater stiffness. Shear wave velocity was higher in the longitudinal compared to the cross-sectional plane but did not differ significantly between the left and right forelimbs. The suspensory ligament was stiffer compared to remaining structures in the cross-sectional plane. Ligaments were stiffer than tendons and the deep digital flexor tendon was stiffer than the superficial digital flexor tendon in the longitudinal plane. Target structures were stiffer in male compared to female horses and stiffness tended to increase with age. ARFI elastography proved to be a feasible and reproducible imaging modality for assessment of distal forelimb tendons and ligaments in horses. Qualitative features derived from stiffness quantification in these structures can be applied to horses with musculoskeletal disorders, as well as to other animal species.
Keywords: equine; ultrasonography; locomotor system